PG68 The use of simulation training for dysphagia assessment- a quality improvement project. (10th November 2020) - Williams, Emma; Toft, Lisa
Abstract : Introduction: Collaboration between Senior Speech and Language Therapists (SLT) and the Simulation Centre at Portsmouth Hospitals NHS Trust, led to a training initiative being developed as a result of safety learning themes identified from incident reporting around issues with swallow assessment. In 2018 the Organisation highlighted an increase in the number of incident reports associated with insufficient practice in assessing a patient swallow amongst the nursing workforce. The SLT and Simulation Centre developed an in situ simulation programme, targeting registered nurses working within Stroke Services and Neurological Rehabilitation settings. Method/Project Description: The 1 hour simulation was delivered within the clinical environment therefore creating accessible training opportunities for staff to attend. Patterson et al (2008) describe in situ simulation as simulation that occurs in the clinical environment in which participants are on duty clinical providers during their actual workday. The 3 scenarios were designed around the safety learning themes identified in the incident reports which created a realistic and interactive session using a live actor to demonstrate different swallowing difficulties. The live actor was a member of the simulation education team and the scenario was piloted prior to undertaking the training initiative. The ambition with this training initiative was to create accessible training opportunities for registered nurses to explore safety learning around swallow assessment and to increase the confidence, competency and compliance with water assessment procedures within Stroke and Neurological Rehabilitation Services. A study by Bray et al 2016 showed a modest association between delays in performing dysphagia screening and the onset of a pneumonia (one of the leading causes of early death post stroke) after hospital admission. Outcome: As a result of the simulation course, 100% of attendees reported an increase in confidence in undertaking a swallow assessment following the training session. A survey undertaken by the Speech and Language Therapist on the ward of 31 individuals from the multidisciplinary team, who have attended Swallow Assessment training, demonstrated that there was continued confidence in identifying signs and symptoms of dysphagia. Discussion/conclusions/recommendations: Due to the success of the water- swallow screen training initiative, further programmes of simulation training have been developed and implemented across the same staffing group to increase the skill and competency in assessing swallowing difficulties when the patient fails the water test. This programme is available for the nursing workforces who have completed and are competent in undertaking the water swallow test. Reference: Bray BD, Smith CJ, Cloud GC, et al. J Neurological Neurosurgery Psychiatry ( 2016) doi:10.1136/jnnp2016-313356. Patterson MD1, Blike G.T., Nadkarni V.M. (2008) in: Henriksen K., Battles J.B., Keyes M.A., Grady M.L., (Ed) Advances in Patient Safety: New Directions and Alternative Approaches (Vol. 3: Performance and Tools). Rockville (MD): Agency for Healthcare Research and Quality. Advances in Patient Safety.